An Updated Review on the Secondary Metabolites and Biological Activities of Aspergillus ruber and Aspergillus flavus and Exploring the Cytotoxic Potential of Their Isolated Compounds Using Virtual Screening. (31st January 2021) - Youssef, Fadia S.; Singab, Abdel Nasser B.
Abstract : The secondary metabolites and biological activities of Aspergillus ruber and Aspergillus flavus were comprehensively reported. About 70 compounds were isolated from both species that belong to different classes using conventional and advanced chromatographic techniques and unambiguously elucidated employing one- and two-dimensional nuclear magnetic resonance (1D and 2D NMR) and high resolution mass spectrometry (HRMS). Some of them displayed promising antiviral, anti-inflammatory, and antioxidant activities. In silico studies were conducted on human cyclin-dependent kinase 2 (CDK-2), human DNA topoisomerase II (TOP-2), and matrix metalloprotinase 13 (MMP-13) in an effort to explore the cytotoxic potential of the diverse compounds obtained from both Aspergillus species. 1, 6, 8-Trihydroxy-4-benzoyloxy-3-methylanthraquinone (23) revealed the most firm fitting with the active pockets of CDK-2 and MMP-13; meanwhile, variecolorin H alkaloid (14) showed the highest fitting within TOP-2 with ∆G equals to −36.51 kcal/mole. Thus, fungal metabolites could offer new drug entities for combating cancer. Relevant data about both Aspergillus species up to August 2020 were gathered from various databases comprising Scifinder (https://scifinder.cas.org/scifinder/ login) for secondary metabolite-related studies; meanwhile, for biology-related articles, data were collected from both PubMed (http://www.ncbi.nlm.nih.gov/pubmed/ ) and Web of Knowledge (http://www.webofknowledge.com ) as well.